2017
DOI: 10.1016/j.neubiorev.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive workload across the spectrum of cognitive impairments: A systematic review of physiological measures

Abstract: Our objective was to identify the physiological measures that are sensitive to assessing cognitive workload across the spectrum of cognitive impairments. Three database searches were conducted: PubMed, PsychINFO, and Web of Science. Studies from the last decade that used physiological measures of cognitive workload in older adults (mean age >65 years-old) were reviewed. The cognitive workload of healthy older individuals was compared with the cognitive workload of younger adults, patients with mild cognitive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 55 publications
(199 reference statements)
2
52
0
Order By: Relevance
“…This increased cognitive demand imposes a greater strain on the available cognitive resources, resulting in a greater cognitive workload exhibited by the subject to continue performing the task ( Kahneman, 1973 ). Psychophysiological studies have identified several neurophysiological measures that can accurately assess the amount of cognitive workload needed to execute a task in real-time ( Ranchet et al, 2017a ). Task-evoked pupillary response (TEPR) accurately reflects cognitive workload through inhibition of the parasympathetic nucleus of Edinger Westphal, resulting in pupil dilation ( Beatty, 1982 ; Eckstein et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This increased cognitive demand imposes a greater strain on the available cognitive resources, resulting in a greater cognitive workload exhibited by the subject to continue performing the task ( Kahneman, 1973 ). Psychophysiological studies have identified several neurophysiological measures that can accurately assess the amount of cognitive workload needed to execute a task in real-time ( Ranchet et al, 2017a ). Task-evoked pupillary response (TEPR) accurately reflects cognitive workload through inhibition of the parasympathetic nucleus of Edinger Westphal, resulting in pupil dilation ( Beatty, 1982 ; Eckstein et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also surprising that young individuals might suffer from severe PTSD symptoms. However, it was documented that younger age and higher fitness level (physical and mental) are associated positively to better cognitive performance performed and conversely, ageing and low level of physical fitness tend to reduce cognitive performance [70][71][72].…”
Section: Health Impairmentsmentioning
confidence: 99%
“…Some studies have suggested that this increased cognitive workload may serve as a predictor of cognitive decline. [4] Several techniques have been developed to measure cognitive workload, including questionnaires, performance outcomes, or physiological measures. The National Aeronautics and Space Administration -Task Load Index (NASA-TLX) [5] is one of the most widely used questionnaires of cognitive workload.…”
Section: Introductionmentioning
confidence: 99%
“…In adults with neurodegenerative conditions, the inability to cope with task demand was even more apparent, resulting in not only an increase in hemodynamic, electrophysiological, and pupillary responses, but also worsening on performance measures. [4] Of those, the pupillary response is particularly interesting since it has been implicated with early tau accumulation in the locus coeruleus (LC) in Alzheimer's disease (AD). [13] Decreased neuronal density of the LC has been associated with cognitive decline in older adults, mild cognitive impairment, and AD.…”
Section: Introductionmentioning
confidence: 99%